2000
DOI: 10.1088/0256-307x/17/3/004
|View full text |Cite
|
Sign up to set email alerts
|

A Scheme of Interferometric Measurement of an Atomic Wave Function

Abstract: A new method to measure an atomic wave function is discussed. It effectively solves the problem of an initially random phase of a travelling-wave laser beam. The relationship between the measured data and the atomic wave function is presented, and the wave function's reconstruction procedure is also analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[1] More detailed analysis showed that large fluctuations in odd-even differences in MoI were observed both in normally deformed and superdeformed nuclei. [4,5] According to the BCS approximation for treating nuclear pairing interaction, the MoI associated with a one-quasiparticle state in an odd-A nucleus should be larger than that of the ground-state configuration of adjacent even-even nucleus by a factor of about 15%. [1] A large fluctuation in odd-even difference in MoIs implies that nuclear MoI depends sensitively on particle number and the contribution to nuclear MoI from the extra odd nucleon plays a crucial role due to blocking effect.…”
Section: Introductionmentioning
confidence: 99%
“…[1] More detailed analysis showed that large fluctuations in odd-even differences in MoI were observed both in normally deformed and superdeformed nuclei. [4,5] According to the BCS approximation for treating nuclear pairing interaction, the MoI associated with a one-quasiparticle state in an odd-A nucleus should be larger than that of the ground-state configuration of adjacent even-even nucleus by a factor of about 15%. [1] A large fluctuation in odd-even difference in MoIs implies that nuclear MoI depends sensitively on particle number and the contribution to nuclear MoI from the extra odd nucleon plays a crucial role due to blocking effect.…”
Section: Introductionmentioning
confidence: 99%